Teacher readiness and understanding in implementing teaching English speaking skills using an ecological approach - Riki Ruswandi; Muhammad Andriana Gaffar; Kikit Elisa Yuniarti (Universitas Islam Malang, 2023)
The purpose of this research is to dig deeper into information about three vocational high schools teachers who have applied the ecological approach in their English teaching process. The ecological approach from the perspective of education is a learning approach that emphasizes contextual learning and focuses on the relationship between teachers, students, and the delivery of teaching materials. Applying the ecological approach to learning English at vocational high school can facilitate teachers in teaching English, especially learning English speaking for students. Teachers have an important role in education because a good education is influenced by teacher competence and teacher readiness in teaching. Speaking skills are one of the skills taught by teachers in schools, speaking skills in Indonesia do not receive enough attention, this is because students have not been able to communicate even in simple English. Based on this, the teacher's readiness to find an appropriate approach to the environmental conditions of students is very influential in teaching English speaking skills and an ecological approach can be a solution in improving students' English speaking skills. This research uses a qualitative research approach, and phenomenological as the research design. The participants in this study were English teachers in tenth grade from the three vocational high schools in Bandung district. This research shows that the ecological approach can improve student English speaking skills in three vocational high schools in Bandung district. It is caused by the teacher's activity who has applied the ecology approach indicator, namely coordination, internalization, media, and development.